Simulation study of pressure wave fluctuation law along fracture under water hammer effect - Jinqi FU; Jun NIAN; Wenxu CHENG (Meikuang Anquan)
In order to analyze the effect of water hammer effect on the propagation law of pulsating water pressure in the fissure, based on the one-dimensional transient flow model with water hammer equation of motion and continuity equation, the jump and fluctuation law of water hammer pressure when the fluid motion state changes instantaneously is studied by numerical simulation. The simulation results show that when the pulsating water flows at a certain flow rate in the fissure, the flow rate is hindered and reduced when it encounters the closure of the fissure end, and the water hammer effect occurs due to the superimposed reflection of inertia and pressure waves. Under the action of water hammer, the fluid pressure will jump instantaneously and hit the coal fissure in the form of rectangular pressure wave. When the pressure wave alternately rises and falls inside the coal fissure, the surge fluid pressure is beneficial to unblock and fissure expansion, forming a positive water hammer feedback; while the superimposed reflection of the pressure wave, the fluid in different flow sections will obstruct each other, resulting in pressure reduction or even negative pressure, forming a negative water hammer feedback. The negative feedback causes the pressure of impact fracture to decrease, but the formed periodic alternating pressure can form fatigue damage to the coal body and derive more new fractures to improve the fracturing effect.